Carbon Footprint Reduction in the Supply Chain - Stefanov, Miroslav (Research Papers, 2020)
The transition to a low-carbon economy requires finding solutions to increase energy efficiency and reduce greenhouse gases. These issues also affect supply chains, as logistics activities are energy-intensive and have a negative impact on the environment through their contribution to climate change. The present article aims to reveal some sustainable logistics practices for reducing the carbon footprint in the Bulgarian supply chains, to determine whether the effect of their implementation is measured and on this basis to identify areas for further research in the field. The presented sustainable logistics practices have been studied on the basis of data from Internet sites and online media, which have been processed with the help of content analysis. The results of the study show that Bulgarian organizations have already applied practices to reduce the carbon footprint in the supply chain - in separate logistics activities, phases and along the entire supply chain, and business organizations with Bulgarian and foreign participation in the capital are aware of their responsibility for climate change. Apart from that, the need for wider application of adequate algorithms for calculating the saved carbon emissions has been stated. Based on the results of the research, recommendations to two groups of stakeholders - business organizations and the scientific community have been provided. Some areas for conducting future research have been identified and appropriate methods for conducting them have been presented.
Keywords: Carbon footprint; Sustainable logistics; Sustainable supply chain management